Manajemen Kelas dalam Meningkatkan Efektivitas Pembelajaran (Studi Kasus di MA Al-Muhtadin Pondok Pesantren Riyadhus Samawi) - Siti Nurlatifah; Nur Yanah; Laili Nur Tsalits Asmoro (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Classroom management is a conscious effort to organize learning process activities systematically, including the preparation of teaching materials, provision of facilities and infrastructure, organizing learning spaces and creating a conducive learning atmosphere so that learning objectives can be achieved. Classroom management efforts lead to the preparation of learning materials, learning facilities and infrastructure, learning space arrangements, controlling student behavior, and improving student achievement and grades. The implementation of classroom management will create an effective, varied, and fun learning atmosphere. The purpose of the research conducted intends to find out (1) To what extent is the implementation of classroom management. (2) Whether the learning process is effective. (3) What are the inhibiting and supporting factors in implementing classroom management. (4) And what efforts are made by teachers and schools in improving the effectiveness of classroom management. The results showed that classroom management has not been carried out optimally, the teacher's teaching method is still monotonous so that it makes students less interested in listening to the material. Then there is still a lack of student discipline. Although the implementation of classroom management is still not optimal, teachers remain enthusiastic and continue to strive to do and implement classroom management optimally, so that what is the goal of the school will be achieved properly. The efforts that teachers will make in implementing classroom management in order to increase the effectiveness of learning are by preparing administrative tasks properly, using varied learning methods and media. And teachers apply student discipline.